PRONUNCIATION PROBLEM OF INDONESIAN LEARNERS IN PRONOUNCING /G/ SOUND AT BHAYANGKARI 01 SENIOR HIGH SCHOOL IN MEDAN - Oktira, Harisa Dwi; Rangkuti, Rahmadsyah (Hikari: Jurnal Bahasa dan Kebudayaan, 2022)
Pronunciation is the production of sounds that are employed to convey meaning. Pronouncing English is a little bit difficult for Indonesian students since they use their mother tongue for their communication. This study was focused on the problem of pronunciation of the /g/ sound in English. The researcher used descriptive qualitative for the research design. The subject of research was the students in grade X MIA 3 that consisted of 27 students. The researcher used the purposive technique to take the sample of the research. The data collection of research was through observation, documentation, and diary notes. The researcher obtained five (5) types of problems in pronouncing /g/ sound, such as /g/ sound before /h/ at the end of words, /g/ sound before /n/ in the middle of words, /g/ sound before /n/ at the beginning of words, /g/ sounds before /e/ at the beginning of words, and /g/ sounds before /i/ at the beginning of words. The mean of data was 14.6, which suggested that there were about 15 students who had a good pronunciation. And the rest students were still had incorrect pronunciation.